2014
DOI: 10.1177/0194599813520291
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Prevalence of Sigmoid Sinus Dehiscence among Patients with and without Pulsatile Tinnitus

Abstract: The prevalence of SSDD in patients with PT was 23%. Among patients with PT, those with SSDD were younger, exclusively female, and presented with objective tinnitus. The prevalence of SSDD among asymptomatic patients in 1 year was 1.2%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 19 publications
7
67
0
Order By: Relevance
“…First, local turbulence originating from acceleration or changes in blood flow may disrupt laminar flow and become the source of VPT. 8 Second, as previous studies have suggested, 19,20 when a pulse-synchronous sound is generated, that sound may be transmitted primarily through the bone conduction route to the inner ear if any discontinuity or weakness is present in the bony (normally) soundproof wall. Vascular PT caused by DSSD/T can be explained by the mechanisms summarized above.…”
Section: Possible Pathophysiological Mechanisms Of Vpt Perception In mentioning
confidence: 99%
See 1 more Smart Citation
“…First, local turbulence originating from acceleration or changes in blood flow may disrupt laminar flow and become the source of VPT. 8 Second, as previous studies have suggested, 19,20 when a pulse-synchronous sound is generated, that sound may be transmitted primarily through the bone conduction route to the inner ear if any discontinuity or weakness is present in the bony (normally) soundproof wall. Vascular PT caused by DSSD/T can be explained by the mechanisms summarized above.…”
Section: Possible Pathophysiological Mechanisms Of Vpt Perception In mentioning
confidence: 99%
“…SSD or diverticula are evident in 23% of patients with PT, and, among PT patients with definable etiologies, 33% had SSD or diverticula. 7,20 However, SSD is also found in as many as 12% of asymptomatic patients, 7 and a bone thickness of less than 0.6 mm over the SS can be falsely interpreted as dehiscence. 3,14 Also, when it is considered that iatrogenic dehiscence of the bony wall of the SS during mastoidectomy usually does not trigger PT, SSD alone may not always cause VPT.…”
mentioning
confidence: 99%
“…Sigmoid sinus dehiscence/ diverticulum (SSDD) is a recently described cause of up to 20 % of PT cases. The symptoms can be improved to some extent with surgical and endovascular interventions [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Three main theories have been proposed for the mechanism of SSDD, the idiopathic intracranial hypertension (IIH) theory [5], blood flow impacting theory [6,3,5], and osteoporosis theory [7]. According to the blood flow impacting theory, SSDD is caused Liu Zhaohui and Dong Cheng contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…According to some reports, between 22% and 48% of patients clinically diagnosed with pulsatile tinnitus of venous origin have a diverticulum or dehiscence of the sigmoid sinus that is detectable on contrastenhanced CT. 6,12 Although treatment for sigmoid sinus wall abnormalities historically has been endovascular embolization, 13 more recently, the open transmastoid approach has become the norm.…”
Section: Discussionmentioning
confidence: 99%